Performance Analysis of Battery Endurance in a Bldc Motor-Based Mini Electric Vehicle: a Case Study at the Electrical Engineering Laboratory, Universitas Pembangunan Panca Budi - Denny Syahputra; Parlin Siagian; Beni Satria (INFOKUM, 2025)
The development of electric vehicle technology continues to experience rapid progress, especially in terms of energy efficiency and power storage systems. One of the main components in an electric vehicle is the battery, which plays a crucial role in determining the vehicle's range, performance, and energy efficiency. This study aims to analyze the battery life of a BLDC (Brushless DC) motor used in a mini electric car prototype. Testing was conducted at the Electrical Engineering Laboratory of Panca Budi Development University with various load scenarios and operating times to evaluate battery life performance. The research method was carried out through an experimental approach by directly measuring voltage, current, temperature, and operating duration using a digital measuring instrument and periodically recording the data. The test results showed that the battery has optimal performance within a certain current range, but experienced a decrease in capacity as the load and operating temperature increased. From the test results, it was concluded that battery life is greatly influenced by operational conditions and charging system management. This study provides an initial overview for the development of a battery management system (BMS) and energy efficiency design in a laboratory-scale mini electric vehicle. Development recommendations are directed at temperature control and load power regulation so that the battery can be used more optimally and sustainably.